2000
DOI: 10.1016/s0010-8545(00)00322-2
|View full text |Cite
|
Sign up to set email alerts
|

Charge-transfer bonding in metal–arene coordination

Abstract: Unusual strength and directionality for the charge-transfer motif (established in solution) are shown to carry over into the solid state by the facile synthesis of a series of robust crystals of the [1:1] donor/acceptor complexes of carbon tetrabromide with the electron-rich halide anions (chloride, bromide, and iodide). X-ray crystallographic analyses identify the consistent formation of diamondoid networks, the dimensionality of which is dictated by the size of the tetraalkylammonium counterion. For the tetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
170
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(195 citation statements)
references
References 114 publications
25
170
0
Order By: Relevance
“…[56] Furthermore, p coordination of naked Cu + is perfectly consistent with well-established concepts for metal-ion coordination, [49,[57][58][59][60] and indeed, crystallographic evidence for h 1 -, h 2 -, and h 6 -coordination of Cu I to arenes [61][62][63][64][65] exists, including examples for preferential p-rather than O-binding of Cu I to p-benzoquinones. [66,67] As the second part of our model system, we investigated…”
Section: A C H T U N G T R E N N U N G (Phoh)]supporting
confidence: 76%
“…[56] Furthermore, p coordination of naked Cu + is perfectly consistent with well-established concepts for metal-ion coordination, [49,[57][58][59][60] and indeed, crystallographic evidence for h 1 -, h 2 -, and h 6 -coordination of Cu I to arenes [61][62][63][64][65] exists, including examples for preferential p-rather than O-binding of Cu I to p-benzoquinones. [66,67] As the second part of our model system, we investigated…”
Section: A C H T U N G T R E N N U N G (Phoh)]supporting
confidence: 76%
“…The planes of the pyrazole rings are inclined to the plane of the adjacent biphenylene unit at angles that range between 67.9 (2) and 112.8 (2) °. The duplicated pattern of bond lengths and angles within the biphenylene core (see Table 1) also parallels those observed in other structurally characterized octa-substituted biphenylenes (Hubig et al, 2000;Le Magueres et al, 2001a;Le Magueres et al, 2001b;Lu et al, 2002). These suggest that there is some bond delocalization in such molecules.…”
Section: Commentsupporting
confidence: 80%
“…Charge transfer from the highest occupied π-orbitals of the arene to the lowest unoccupied 2e and 2a 1 orbitals of Cr(CO) 3 partially breaks the C−C bonds, thus explaining the observed expansion of the aromatic ring and the increase in bond length alternation in the benzene ring of (η 6 -C 6 H 6 )Cr(CO) 3 . Because of the loss of π electron density in the ring, one should expect a partial disruption of aromaticity in the benzene ring of (η 6 -C 6 H 6 )Cr(CO) 3 in comparison to free benzene, as discussed by Hubig et al [103] and not the increase of aromaticity observed by Mitchell and co-workers [98][99][100][101]. Indeed, all indices used by us [97], except NICS(0) and NICS(1), showed that there is a clear reduction of the aromaticity of benzene upon coordination to the Cr(CO) 3 complex.…”
Section: B) C) A)mentioning
confidence: 94%
“…It is widely accepted that the structure, reactivity, and aromaticity of the benzene ring are altered significantly upon complexation with the chromium tricarbonyl complex. Thus, after coordination the ring expands, loses its planarity (the hydrogen atoms of the benzene ring slightly bent towards the Cr(CO) 3 fragment [102]), and shows an increased difference between alternated short and long C-C bonds [103]. These changes can be rationalized taking into account the nature of the bond between the arene and the metal in (η 6 -arene)tricarbonylchromium complexes [104].…”
Section: B) C) A)mentioning
confidence: 99%